Industrial Relations Education in Canada: The Perspective of Vocational/Technical Educators - Fraser, C. (Relations industrielles / Industrial Relations, 1978)
This paper discusses the relevancy of industrial relations education in the formal education Systems in Canada, and through analysis of a survey of vocational and technical educators, examines their perceptions of IR education in Canada generally, and in vocational/technical institutions specifically.